Effect of Music Therapy and Sound Isolation on the Comfort of Mechanically Ventilated Patients - Sinem Çalışkan; Esra Akın; Mehmet Uyar (Galenos Yayinevi, 2024)
Objective: This study was conducted experimentally to examine the effect of music therapy and sound isolation on the comfort of mechanically ventilated patients. Materials and Methods:The study was conducted in the anesthesiology and reanimation intensive care unit of a university hospital between November 2019 and January 2020. Three different interventions were applied to n=24 patients who constituted the research sample. Each patient listened to Western Classical Music and Nihavend magam Turkish Classical Music separately for 60 minutes (min) and received an intervention of sound isolation for 60 min through a special headset. Results: The mean age of the patients participating in the study was 64.88±14.05. Of the patients, 66.7% were male, 79.2% were married, and 45.8% were illiterate. Patients' systolic and diastolic blood pressures, pulse rate, respiratory rate, Critical-Care Pain Observation Tool score, and scores on agitation and anxiety sub-dimensions of the American Association of Critical Care Nurses Sedation Assessment scale were influenced by Western Classical Music, Nihavend maqam Turkish Classical Music, and sound isolation. No difference was found among the three different implementation interventions. Conclusion: Music therapy and sound isolation interventions administered to mechanically ventilated patients positively affected the hemodynamic parameters of the patients and reduced the severity of pain perceived by the patients and the need for sedation. In this context, the most important finding of the study was that an intervention that eliminates noise in the intensive care environment for mechanically ventilated patients increases the comfort level of the patients. Another important and critical result of this research was that music therapy also acts as an intervention without noise stimuli.